Global prevalence of antibiotic resistance in paediatric urinary tract infections caused by Escherichia coli and association with routine use of antibiotics in primary care: systematic review and meta-analysis - Bryce,A; Hay,AD; Lane,IF; Thornton,HV; Wootton,M; Costelloe,C (British Medical Journal, 2016)
Objectives To systematically review studies investigating the prevalence of antibiotic resistance in urinary tract infections caused by Escherichia coli in children and, when appropriate, to meta-analyse the relation between previous antibiotics prescribed in primary care and resistance.Design and data analysis Systematic review and meta-analysis. Pooled percentage prevalence of resistance to the most commonly used antibiotics in children in primary care, stratified by the OECD (Organisation for Economic Co-operation and Development) status of the study country. Random effects meta-analysis was used to quantify the association between previous exposure to antibiotics in primary care and resistance.Data sources Observational and experimental studies identified through Medline, Embase, Cochrane, and ISI Web of Knowledge databases, searched for articles published up to October 2015.Eligibility criteria for selecting studies Studies were eligible if they investigated and reported resistance in community acquired urinary tract infection in children and young people aged 0-17. Electronic searches with MeSH terms and text words identified 3115 papers. Two independent reviewers assessed study quality and performed data extraction.Results 58 observational studies investigated 77 783 E coli isolates in urine. In studies from OECD countries, the pooled prevalence of resistance was 53.4% (95% confidence interval 46.0% to 60.8%) for ampicillin, 23.6% (13.9% to 32.3%) for trimethoprim, 8.2% (7.9% to 9.6%) for co-amoxiclav, and 2.1% (0.8 to 4.4%) for ciprofloxacin; nitrofurantoin was the lowest at 1.3% (0.8% to 1.7%). Resistance in studies in countries outside the OECD was significantly higher: 79.8% (73.0% to 87.7%) for ampicillin, 60.3% (40.9% to 79.0%) for co-amoxiclav, 26.8% (11.1% to 43.0%) for ciprofloxacin, and 17.0% (9.8% to 24.2%) for nitrofurantoin. There was evidence that bacterial isolates from the urinary tract from individual children who had received previous